Sosialisasi Penggunaan Pestisida Ramah Lingkungan Beauveria Bassiana Di DAS Kromong II Kecamatan Pacet Kabupaten Mojokerto - Putra, Dimas Ganda Permana; Fitriyani, Zenita Afifah; Ardiyanto, Farhur Rijal; Khusumawati, Titik; Alam, Megawati Citra (Pakis Journal Institute, 2025)
The intensification of modern agricultural productivity is often accompanied by a high dependency on synthetic pesticides, which, despite their immediate effectiveness, contribute to long-term ecological degradation, chemical residue contamination, and the accelerated development of pest resistance. One sustainable alternative approach involves the use of biological control agents, such as Beauveria bassiana, an entomopathogenic fungus capable of selectively infecting and killing various insect pest species in an environmentally friendly manner. This community service initiative was conducted in Candiwatu Village, Pacet Subdistrict, Mojokerto Regency, with the objective of transferring knowledge and technical skills regarding the formulation and field application of B. bassiana to local farmer groups. The implementation methods included initial observation of pesticide-related environmental issues in the Kromong II watershed area, stakeholder engagement, and participatory training sessions encompassing the concept of biopesticides, spore production techniques, and practical application strategies. The results indicated an increase in farmers' understanding of both the ecological and technical aspects of B. bassiana utilization, along with the formation of positive perceptions toward its efficacy and safety. By actively involving farmers in hands-on educational and demonstrative processes, this program contributed to fostering the adoption of biological control technologies at the local level and to establishing an institutional foundation for more adaptive, resilient, and sustainable agricultural systems.